Food security in families of Yurimaguas, Peru: Characteristics and associated factors (Agroindustrial Science, 2024)
Food security is sufficient access to safe and nutritious foods to satisfy nutritional needs and personal preferences, and to lead a healthy and active life. Objectives. To determine food security in 160 households of human settlement of Yurimaguas district, Loreto department, Perú and factors associated with it. Methods. The selected households had among their members at least one child under 18 years of age and an unmet basic need, which for all of them, did not have the sewage service. In these households, the Latin American and Caribbean Food Security Scale (ELCSA) was applied, consisting of 15 items and a sociodemographic and socioeconomic survey. The households were classified as food secure, or mildly, moderately or severely food insecure. Results. Among households, 3.1% were classified as food secure and 96.9% as food insecure (78.8% as mildly insecure, 16.9% as moderately insecure and 1.2% as severely insecure). Food- insecure households had a greater number of minors, mothers with a lower educational level and the daily expenditure in food was lower in comparison with food-secure households. Conclusions. A very high percentage of the households surveyed in the study area were food insecure, although mostly mild. Associated with the number of minors in the home, the mother's education and daily spending on food purchases.
Keywords: Food insecurity; ELCSA; urban settlement; associated factors; Perú